2020
DOI: 10.1155/2020/9460364
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activity and Functional Connectivity in Unilateral Sudden Sensorineural Hearing Loss

Abstract: Background. Sudden sensorineural hearing loss (SSNHL) is an otologic emergency and could lead to social difficulties and mental disorders in some patients. Although many studies have analyzed altered brain function in populations with hearing loss, little information is available about patients with idiopathic SSNHL. This study is aimed at investigating brain functional changes in SSNHL via functional magnetic resonance imaging (fMRI). Methods. Thirty-six patients with SSNHL and thirty well-matched normal hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…In contrast, Xu et al (2016) detected enhanced Cp and weakened Lp in unilateral SNHL. Chen et al found that tinnitus patients have increased global efficiency, local efficiency, and cluster coefficient, indicating generally heightened connectivity of the network, which was consistent with the increased global efficiency of our study ( Chen et al, 2020 ). These discrepancies might result from (1) various kinds of hearing loss, such as side, duration, and severity; (2) different nodes of network construction and our study chose 90 nodes from the AAL atlas; (3) differences in accompanied symptoms, such as tinnitus and vertigo.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Xu et al (2016) detected enhanced Cp and weakened Lp in unilateral SNHL. Chen et al found that tinnitus patients have increased global efficiency, local efficiency, and cluster coefficient, indicating generally heightened connectivity of the network, which was consistent with the increased global efficiency of our study ( Chen et al, 2020 ). These discrepancies might result from (1) various kinds of hearing loss, such as side, duration, and severity; (2) different nodes of network construction and our study chose 90 nodes from the AAL atlas; (3) differences in accompanied symptoms, such as tinnitus and vertigo.…”
Section: Discussionsupporting
confidence: 91%
“…When the central auditory system input is reduced, other sensory inputs would be enhanced correspondingly ( Lomber et al, 2010 ). Previous fMRI studies demonstrated that there may exist transmodal neural change in the visual and sensory system in patients with sensorineural hearing loss (SNHL), which reflects the compensation of brain function ( Lomber et al, 2010 ; Chen et al, 2020 ). In this study, CBF increase in visual-related areas, suggesting that there may be similar visual compensation in patients with SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies reported no significant difference in the ReHo value between the ISSNHL patients and the healthy controls in any brain region. The various neuroimaging methods employed and the participants’ heterogeneity may have contributed to the inconsistent results ( Cai et al, 2020 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%